Synthesis and Biological Activities of 3-Substitued-1-Tetralone Derivatives: Part-I - Naidu, A.V.; Dave, M.A. (Asian Journal of Chemistry, 2010)
2-Amino-4,5-dihydronaphtho-[1,2-d]-thiazole was condensed with salicylaldehyde to get Schiff base, it was reduced and cyclized to get 2H -3-( 4,5-dihydronaphth-[1,2-d]-thiazole)-3,4-dihydro-1,3- benzoxazine. The Schiff base with DMSO-I2-H2SO4 gave 2H- 3-( 4,5-dihydronaphtho - [1,2-d]-thiazole) - 3,4-dihydro - 1,3-benzoisoxazole. Synthesis of 6-methoxy methyl naphtho-[1,2-d][1,2,3]-thiazole- 4-carboxylate, 6-methoxynaphtho-[ 1 ,2-d] [1,2,3]-thiazole- 4-hydrazo-carbonyl and 6-methoxynaphtho-[I1,2-d][1,2,3]-thiazole-4- arylidene hydrazocarbonyl prepared from the starting compound 3- carbmethoxy-7 -methoxy-1-tetralone.